Molecular tools for genome editing in plants: a synthetic overview - Nicolau Brito da Cunha; Michel Lopes Leite; Júlio Carlyle Macedo Rodrigues; Jéssica Carrijo; Fabrício Falconi Costa; Simoni Campos Dias; Elíbio Leopoldo Rech; Giovanni Rodrigues Vianna (Vegetable Research)
The modification of plant genomes is an essential step towards the development of new crops to increase food production. Initially, genome modification relied on conventional plant breeding and the introduction of genetic traits using crossing techniques to generate new varieties. In the 1980s, trans and cis modification allowed the incorporation of specific traits into plant genomes, largely due to the development of DNA delivery systems such as Agrobacterium and biolistics. This technological breakthrough has boosted a second generation of genetically modified crops that have had a major impact on agriculture. However, the stochastic nature of the DNA delivery systems, with little control over where the genome modification occurred, required regulatory measures to ensure environmental, human, and animal safety, which has hindered the ability and speed to generate new and more adapted varieties. New technological advances have made it possible to increase the precision of genome modifications leading to a third generation of agricultural products. These technological advances rely on enzymes targeting specific genomic regions, making it possible to introduce mutations and new traits into the plant genome. Meganucleases, zinc-finger nucleases, transcription activator-like effector nucleases, and CRISPR/Cas9 are valuable tools that allow for specific genomic modifications. These tools have made it possible to develop new, safer varieties in a shorter timeframe. In this review, we explore the functional mechanisms of these new breeding tools, their advantages and drawbacks, and their potential to explore metabolic engineering and synthetic biology in plants.